2009
DOI: 10.1038/eye.2009.152
|View full text |Cite
|
Sign up to set email alerts
|

Retinal vascular occlusions occur more frequently in the more affected eye in exfoliation syndrome

Abstract: Purpose To evaluate the relationship between retinal vascular occlusions (RVOs) and exfoliation syndrome (XFS) in a cohort of patients with the two conditions. Methods We reviewed the records of patients with XFS with or without glaucoma and any type of RVO between 1983 and 2007. Patients with prior incisional surgery or a history of uveitis were excluded. Data collected included demographics, systemic comorbidities, type of RVO, and intraocular pressure (IOP) before the RVO. Slit-lamp biomicroscopy regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 41 publications
3
12
1
Order By: Relevance
“…Regarding demographic and ocular parameters, CRVO was more prevalent in the elderly and middle to late stage glaucoma cases with large cupping. Although we do not have exfoliative glaucoma cases in our study, Prata et al manifested that retinal vascular occlusion in patients with exfoliation syndrome occurs most frequently in the affected or more severely affected eye [12]. This is in agreement with the consensus that large cupping in glaucoma patients is vulnerable to CRVO [3, 12].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding demographic and ocular parameters, CRVO was more prevalent in the elderly and middle to late stage glaucoma cases with large cupping. Although we do not have exfoliative glaucoma cases in our study, Prata et al manifested that retinal vascular occlusion in patients with exfoliation syndrome occurs most frequently in the affected or more severely affected eye [12]. This is in agreement with the consensus that large cupping in glaucoma patients is vulnerable to CRVO [3, 12].…”
Section: Discussionsupporting
confidence: 91%
“…Although we do not have exfoliative glaucoma cases in our study, Prata et al manifested that retinal vascular occlusion in patients with exfoliation syndrome occurs most frequently in the affected or more severely affected eye [12]. This is in agreement with the consensus that large cupping in glaucoma patients is vulnerable to CRVO [3, 12]. Moreover, the incidence of the ischemic CRVO type in pre-existing glaucoma was similar to that in the non-glaucoma population.…”
Section: Discussionsupporting
confidence: 89%
“…8,9 The discovery that common variants of LOXL1 are present in 99% of XFS cases represents a significant advance in understanding this condition. 10 However, 80% of controls also harbor these variants and the ratio of cases to controls with trait-related variants is fairly similar in regions where XFS is hyper-endemic 11 and regions where the condition is relatively rare.…”
Section: Introductionmentioning
confidence: 99%
“…Prata et al also found that RVO occurred more frequently in patients with the exfoliation syndrome, the most common identifiable cause of OAG worldwide [75]. The reason why an RVO occurred most often in the affected or more severely affected eye in patients with exfoliation syndrome could possibly be attributed to a combination of factors.…”
Section: Retinal Vein Occlusion As Risk Factor For Open Angle Glaucomamentioning
confidence: 96%